2012
DOI: 10.1371/journal.pone.0037971
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Specific Lactobacilli Levels Decreases Inflammation and Muscle Atrophy Markers in an Acute Leukemia Mouse Model

Abstract: The gut microbiota has recently been proposed as a novel component in the regulation of host homeostasis and immunity. We have assessed for the first time the role of the gut microbiota in a mouse model of leukemia (transplantation of BaF3 cells containing ectopic expression of Bcr-Abl), characterized at the final stage by a loss of fat mass, muscle atrophy, anorexia and inflammation. The gut microbial 16S rDNA analysis, using PCR-Denaturating Gradient Gel Electrophoresis and quantitative PCR, reveals a dysbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
236
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(251 citation statements)
references
References 49 publications
10
236
1
4
Order By: Relevance
“…Lactobacilli beneficial effect seems to be bacterial strain-or species-dependent. Indeed, administration of L. acidophilus NCFM to leukemic mice with cachexia did not reduce systemic inflammation and muscle atrophy markers (Bindels et al, 2012). Whether the anti-atrophy effect of specific lactobacilli are directly dependent on their immunomodulatory properties remains to be determined.…”
Section: Muscle Wasting and Gut Microbiota In Cachexiamentioning
confidence: 96%
See 2 more Smart Citations
“…Lactobacilli beneficial effect seems to be bacterial strain-or species-dependent. Indeed, administration of L. acidophilus NCFM to leukemic mice with cachexia did not reduce systemic inflammation and muscle atrophy markers (Bindels et al, 2012). Whether the anti-atrophy effect of specific lactobacilli are directly dependent on their immunomodulatory properties remains to be determined.…”
Section: Muscle Wasting and Gut Microbiota In Cachexiamentioning
confidence: 96%
“…Levels of caecal Lactobacillus spp., a bacterial genus known for its immunomodulatory properties, were decreased. Lactobacilli species were differentially affected: L. reuteri and L. gasseri/johnsonii were decreased whereas L. murinus/animalis remained unaffected (Bindels et al, 2012). Interestingly, restoring gut lactobacilli by oral supplementation with L. reuteri 100-23 and L. gasseri 311476 reduced the levels of systemic inflammatory cytokines, such as interleukin (IL)-6, IL-4 and monocyte chemoattractant protein (MCP)-1.…”
Section: Muscle Wasting and Gut Microbiota In Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model for leukemia-induced cachexia, a decrease in Lactobacillus reuteri and L. gasseri was shown compared to healthy controls. Interestingly, supplementation of these Lactobacillus species resulted in a reduction in atrophy markers and inflammatory cytokines [78].…”
Section: Microbial Characteristics In Undernutritionmentioning
confidence: 99%
“…A microbial signature common in both mouse models including the Entero‐bacteriaceae family/Escherichia genus, Lactobacillus genus and Parabacteroides goldsteinii/ASF 519 species were presented. Interestingly, a highly significant negative correlation was found between the level of lactobacilli in the cecal content and the atrophy marker expression in the gastrocnemius muscle (Atrogin‐1, MurF1, LC3 and Cathepsin L) 9. Moreover, they impressively demonstrated that cancer cachexia was associated with profound alterations of the gut microbiota in two animal models.…”
Section: Introductionmentioning
confidence: 92%